4-Methoxy-ortho-phthalaldehyde: a promising derivatizing agent for the fluorimetric evaluation of histamine in seafood - Clémence Moitessier; Khémesse Kital; Pierre-Edouard Danjou; Francine Cazier-Dennin (Talanta Open, 2020)
Histamine, the molecule associated with food poisoning, is nowadays considered as a reliable marker of seafood freshness and therefore its rapid and easy quantification appears critical. Existing method like HPLC or direct fluorimetric analysis employing ortho-phthalaldehyde (OPA) can be time-consuming and tedious. To overcome this problem, we propose in this paper to evaluate the application potential of 4-methoxy-ortho-phthalaldehyde (MO-OPA) for the rapid and easy evaluation of histamine in seafood samples. For this purpose, the histamine complexation conditions were studied by molecular fluorescence spectroscopy using MO-OPA as derivatization agent and then compared with the reference compounds: OPA. MOPA proved to be superior to OPA for histamine detection in terms of linearity range (1.10−6–1.10−4 mol.L−1, R²>0.99, n = 10) and detection limit (9.5.10−7 mol.L−1). The optimal conditions were next applied to the analysis of histamine in a mixture of biogenic amines standards and finally on real samples of yellowfin tuna of known histamine concentration.